Preparation method of low-carbon self-leveling mortar for mine
Patent Information
- Application Number
- CN202410723810.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-05
AI Technical Summary
其主要化学成分为CaSO4·2H2O,相比天然石膏有较高的含水量,但是磷石膏中含有一些杂质,为其使用造成了阻碍
(1)本发明提供一种矿山用低碳自流平砂浆的制备方法,它依靠重力及高流动性达到自找平的功能性建筑砂浆,与水泥基矿山修复砂浆相比,本发明的矿山修复砂浆具有体积稳定性好,水化硬化快等优点,大大降低了生产成本,拓宽了固废资源化利用的途径,提升了新型低碳矿山修复砂浆的后期强度和与外加剂的相容性,实现了新型低碳矿山修复砂浆生产过程的高效和科学性稳定控制。
Smart Images

Figure CN118652094B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of comprehensive resource utilization technology, and in particular relates to a method for preparing low-carbon self-leveling mortar for mining. Background Technology
[0002] Mine restoration mortar is a type of mortar used for mine restoration, and its application and performance are similar to self-leveling mortar materials used in building construction. Traditional self-leveling mortar is a dry powder material specifically used for indoor floor leveling, made by uniformly mixing high-strength gypsum, fine aggregate (quartz sand), cement, water-reducing agent, activator, etc. The gypsum is generally type A or type β hemihydrate gypsum, or subtype anhydrite, obtained by firing or steam pressing grade 1 dihydrate gypsum with a purity >90% at 650℃~750℃. The additives are all common chemical products and their dosage is <1%.
[0003] In the 1960s, Europe began using gypsum-based flooring materials. However, research and development of self-leveling mortar in my country only started in the 1990s, and progress has been slow due to limitations in technology and cost. my country has abundant reserves of anhydrite, but its dense structure, slow dissolution, and low hydration activity severely restrict its efficient utilization.
[0004] Phosphogypsum is a slurry-like mixture produced during the production of phosphate fertilizers, resulting from the reaction of phosphate rock with sulfuric acid. It contains liquid phosphoric acid and solid calcium sulfate residue. After filtration and washing, H3PO4 and CaSO4 are separated, and the resulting CaSO4 residue is phosphogypsum. Its main chemical component is CaSO4·2H2O. Compared to natural gypsum, it has a higher water content, but phosphogypsum contains some impurities, which hinder its use. These impurities mainly include soluble impurities, insoluble impurities, and eutectic phosphorus.
[0005] How to utilize phosphogypsum and other diverse solid wastes to prepare mortar materials with excellent construction and mechanical properties, thereby greatly reducing environmental pollution, turning waste into treasure, and achieving significant economic and social benefits, is a technical challenge that urgently needs to be solved. Summary of the Invention
[0006] This invention effectively utilizes effective components from papermaking sludge, marble tailings, quartz sludge, copper tailings, lithium slag, vanadium-titanium ore slag, stainless steel slag, copper slag, coal gasification slag, aluminum ash slag, phosphogypsum, waste apple tree branches and waste trees, waste cement slurry, traditional Chinese medicine residue and tofu wastewater, as well as waste wind turbine blades, thus enabling the effective utilization of chemical waste, steel waste, coal-based waste, agricultural waste, and non-ferrous metallurgical waste. The resulting mine restoration mortar exhibits excellent workability and mechanical properties, significantly reducing production costs. This invention not only achieves the synergistic utilization of multi-source solid waste, realizing energy conservation and environmental protection, but also "treats waste with waste," generating high economic value from solid waste-based materials while achieving green and sustainable development in the construction, mining, and metallurgical industries.
[0007] This invention provides a method for preparing low-carbon self-leveling mortar for mining, the method comprising the following steps: S1. Pretreatment of papermaking sludge: After removing impurities, the papermaking sludge is placed in a cool place to dry, so that its moisture content is 10~20%, and then dried to constant weight. It is then dispersed into ≤2mm particles by ball mill for later use. S2. Pretreatment of marble tailings: After removing impurities, place the marble tailings in a cool place to dry, so that the moisture content is 10~20%, and then dry them to constant weight. Then crush them into ≤2mm particles for later use. S3. Pretreatment of quartz sludge: After removing impurities, place the quartz sludge in a cool place to dry, so that its moisture content is 10~20%, and then dry it to constant weight. Then disperse it into ≤2mm particles by ball mill for later use. S4. Pretreatment of copper tailings / lithium slag: The copper tailings and lithium slag are dried to constant weight, crushed into ≤2mm particles by a crusher, and then the copper tailings and lithium slag are mixed at a mass ratio of 1~2:1~2 to obtain a mixture. S5. Pretreatment of vanadium-titanium ore slag / copper slag / stainless steel slag: The vanadium-titanium ore slag, copper slag and stainless steel slag are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the vanadium-titanium ore slag, copper slag and stainless steel slag are mixed in a mass ratio of 1~2:1~2:1~2 to obtain a mixture. S6. Pretreatment of coal gasification ash / aluminum ash: The coal gasification ash and aluminum ash are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the coal gasification ash and aluminum ash are mixed at a mass ratio of 1~2:1~2 to obtain a mixture. S7. Pretreatment of phosphogypsum: (1) Dry the phosphogypsum to constant weight, disperse it to ≤2mm particles by ball milling to obtain powder 1; (2) Calcine powder 1, and after cooling the calcined powder, mix it with the uncalcined powder 1 at a mass ratio of 1~2:1~2 and grind it in a ball mill to a specific surface area of 350~450m². 2 / kg, and then put the ground material into a sealed barrel to age for three days to obtain powder 2; S8. Pretreatment of waste apple branches and waste trees: The peeled and pruned waste apple branches and waste trees are dried by forced air drying until the moisture content is ≤10%, and then placed in a dry distillation kettle for carbonization using high-temperature flue gas; then crushed to a particle size of ≤2mm by a crusher, and the crushed waste apple branches and waste trees particles are mixed at a mass ratio of 1~4:1~3 to obtain a carbon particle mixture of ≤2mm. S9. Compression Molding: A mixture is prepared by mixing the powders from S1, S2, S3, S4, S5, S6, and S7 in a weight ratio of 25-35%:25-35%:10-20%:5-10%:5-10%:5-8%:3-5%. 5-8% (by weight) of carbon particles are added to this mixture, and after thorough mixing, it is ground to a specific surface area of 300-500 m². 2 / kg, transfer to mortar mixer, add 8~10% water by weight of the mixture, stir well, put into mold, press into patties, and dry the patties at 100℃ for 40min; S10. High-temperature calcination: The cake dried in step S9 is calcined at high temperature. After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. S11. Pretreatment of low-carbon powder 3: The high-temperature calcined product in step S10 is crushed to ≤2mm particles by a crusher, and then ground in a ball mill to a specific surface area of 450~550m². 2 / kg, yielding 3 kg of low-carbon powder; S12. Waste cement slurry pretreatment: After screening and natural drying, waste cement slurry with a particle size <5cm is dried to constant weight, crushed to ≤2mm particles by a crusher, and then fed into a ball mill for grinding to a specific surface area of 450~550m². 2 / kg, yielding 4g of powder; S13. Pretreatment of Chinese herbal medicine residue: Dry the Chinese herbal medicine residue to constant weight; mix 11% kerosene and 96% concentrated sulfuric acid at a volume ratio of 2-3:1 to obtain a mixed solution; mix the Chinese herbal medicine residue and the mixed solution at a mass ratio of 25-30:100 and stir evenly; soak at 45-55℃ for 3-5 hours; cool to room temperature; neutralize the separated solvent with a mass percentage concentration of 25%-28% NaOH solution to a pH of 7-9; filter to obtain the Chinese herbal medicine residue extract. S14. Pretreatment of tofu wastewater: Add stainless steel slag to the refrigerated tofu wastewater for flocculation treatment. The flocculation time is 4-6 hours. Filter to obtain tofu wastewater filtrate. S15. Preparation of water-reducing agent: The pretreated Chinese herbal medicine residue extract in S13 and the tofu wastewater filtrate in S14 are mixed in a volume ratio of 1~2:1~2 to prepare a water-reducing agent. S16. Pre-treatment of waste wind turbine blades: The cut waste wind turbine blades are shredded and the fibers with a length of 10~13mm and a diameter of 8~11μm are screened out for later use. S17. Preparation of mine restoration mortar: Powder 2 from S7, powder 3 from S11, and powder 4 from S12 are mixed evenly in a mortar mixer at a mass ratio of 59~67%:13~17%:20~24% to obtain mine restoration mortar mixed powder. Add water at a mass ratio of 38~42% of the mixed powder and mix evenly. Then add water-reducing agent at a mass ratio of 0.1~0.3% of the mixed powder and mix evenly. Finally, add fiber at a mass ratio of 1~3% of the mixed powder and mix evenly to obtain mine restoration mortar.
[0008] Optionally, the calcination of powder 1 in step S7 is as follows: heating to 140℃~160℃ at a heating rate of 5℃ / min and holding at that temperature for 50~70min.
[0009] Optionally, in step S8, carbonization is performed with the temperature of the high-temperature flue gas being 500~700℃ and the carbonization time being 3~6h.
[0010] Optionally, the powder in S1, the powder in S2, the powder in S3, the powder in S4, the mixture in S5, the mixture in S6, and the powder 1 in S7 in step S9 are mixed in a weight ratio of 35%:25%:10%:10%:8%:8%:4% to obtain the mixture.
[0011] Optionally, in step S9, the pressing pressure is 15~25 MPa, the cake thickness is 1~2 cm, and the diameter is 4~6 cm.
[0012] Optionally, the high-temperature calcination in step S10 is as follows: the temperature is increased to 700°C at a heating rate of 5°C / min, and then held for 20 min; then the temperature is increased to 1050~1250°C at a heating rate of 10°C / min, and held for 30~50 min.
[0013] Optionally, the cooling in step S10 includes first cooling to 800°C at a wind speed of 18-20°C / min, and then cooling to room temperature at a speed of not less than 50°C / min. The purpose is to improve the quality of the low-carbon powder by controlling the cooling temperature; first, slow cooling controls the formation of C2S in the powder, and then rapid cooling yields low-carbon powder with excellent performance in the early, middle, and late stages.
[0014] Optionally, in step S10, the high-temperature calcination is performed by heating from 700°C to 1150°C at a heating rate of 10°C / min and holding at that temperature for 40 minutes.
[0015] Optionally, in step S17, the mass ratio of powder 2 in S7, powder 3 in S11, and powder 4 in S12 of the mine restoration mortar mixture is 63%:15%:22%.
[0016] Optionally, in step S17, 0.2% by weight of water-reducing agent is added to the mixed powder.
[0017] The beneficial technical effects of the present invention are as follows: (1) This invention provides a method for preparing low-carbon self-leveling mortar for mining. It is a functional building mortar that achieves self-leveling by relying on gravity and high fluidity. Compared with cement-based mine repair mortar, the mine repair mortar of this invention has the advantages of good volume stability and fast hydration and hardening, which greatly reduces production costs, broadens the way of solid waste resource utilization, improves the later strength of the new low-carbon mine repair mortar and its compatibility with admixtures, and realizes efficient and scientific stable control of the production process of the new low-carbon mine repair mortar.
[0018] (2) The mine restoration mortar prepared by the present invention using 100% solid waste includes: papermaking sludge, marble tailings, quartz sludge, copper tailings, lithium slag, vanadium-titanium slag, copper slag, stainless steel slag, coal gasification slag, aluminum ash slag, phosphogypsum, waste apple tree branches, waste trees, Chinese medicine residue, waste cement slurry, waste wind turbine blades, etc. The physical and mechanical properties (workability and mechanical properties) of the mine restoration mortar meet the test index requirements of "Gypsum-based Self-leveling Mortar" JC / T 1023-2021. Its radioactivity meets the test index requirements of "Limits of Radionuclides in Building Materials" GB 6566-2010. At the same time, its safety meets the requirements of "Groundwater Quality Standard" GB / T 14848-2017. The present invention improves the utilization rate of industrial solid waste raw materials, can significantly reduce the production cost of enterprises, and has significant economic and social environmental benefits.
[0019] (3) The raw materials used in the mine restoration mortar proposed in this invention replace those used in traditional production processes. Specifically, it utilizes low-carbon powders prepared from chemical solid waste, non-metallic mine solid waste, power industry solid waste, non-ferrous metallurgical solid waste, iron and steel solid waste, construction solid waste, coal-based solid waste, and agricultural solid waste. These powders, combined with the mineral composition and content characteristics of novel low-carbon cement clinker, replace silicate cement clinker. Furthermore, it utilizes chemical solid waste and non-metallic mine solid waste to replace all calcareous raw material limestone. It also utilizes quartz sludge and copper tailings as high-silica raw materials to replace traditional siliceous raw materials. Finally, it utilizes non-ferrous metal industry... Solid waste and coal-based solid waste are used as aluminum raw materials, non-ferrous metal industry solid waste and steel solid waste are used as iron raw materials, and phosphogypsum is used as a sulfur raw material to replace gypsum. The proteins, amino acids, fats, and carbohydrates in pretreated tofu wastewater and traditional Chinese medicine residue provide surfactants for the mine restoration mortar system. These surfactants can form an adsorption film on the particle surface, thereby improving the dispersion state between mine restoration mortar particles, reducing inter-particle friction and adhesion, maintaining the fluidity of the mine restoration mortar while reducing the amount of binder required, and improving the strength and durability of the mine restoration mortar. The synergistic effect among multiple solid waste sources makes the composition of the mine restoration mortar more scientifically standardized and more suitable for actual production processes.
[0020] (4) This invention, through specific crystalline phase structure design and regulation, enables the low-carbon powder made from the obtained high-temperature calcination product to possess higher physical and mechanical properties in a short time, significantly superior to existing ordinary silicate cement clinker. Simultaneously, the powder 3 described in this invention also exhibits excellent characteristics such as high strength, rapid setting, rapid hardening, low carbon content, low alkali content, and low chloride ion content. This can shorten the construction cycle and is of great significance for mine restoration, emergency construction and repair of municipal engineering projects, building decoration, road and bridge repair, as well as for material and wartime emergency reserve technology.
[0021] (5) In the process of preparing low-carbon powder using calcareous materials (papermaking sludge, marble tailings), siliceous materials (quartz sludge, copper tailings, lithium slag), iron-aluminate materials (copper slag, stainless steel slag, vanadium-titanium ore slag, coal gasification ash slag, aluminum ash slag), and sulfurous materials (phosphogypsum) as raw materials, by reasonably controlling the particle size, molding conditions, calcination time, and heat preservation time, the four conditions are optimally matched and synergistic, which can enable the low-carbon powder to form a specific crystal phase structure, so that the powder has excellent early, middle and late stage performance and can replace silicate cement clinker.
[0022] (6) The low-carbon powder prepared by the present invention has a significant carbon reduction effect. Its firing process incorporates papermaking sludge and carbon particles, which reduces the firing temperature by 100°C compared to silicate cement clinker and reduces energy consumption by more than 10%. At the same time, the powder uses all solid waste raw materials in the firing process and does not use limestone, which reduces CO2 emissions by more than 20%. This can significantly reduce the production cost of enterprises and is conducive to the realization of the "dual carbon" target of the building materials industry. It has good economic, social and ecological environmental benefits.
[0023] (7) The present invention can purposefully and stably control the composition and content ratio of each mineral in the powder. Its performance is excellent and can reach and exceed the existing silicate cement clinker. It is expected to be widely used and replace traditional silicate cement in large quantities, thus helping the cement industry achieve low-carbon and sustainable development. Attached Figure Description
[0024] Figure 1 The image shows the XRD pattern of the high-temperature calcination product in Example 2 of this invention.
[0025] Figure 2 This is an SEM image of the high-temperature calcination product in Embodiment 2 of the present invention.
[0026] Figure 3 This is the EDS diagram of the high-temperature calcination product in Example 2 of the present invention.
[0027] Figure 4 This describes the development law of the compressive strength of powder 2 in embodiment 2 of the present invention.
[0028] Figure 5 This invention illustrates the effect of water-reducing agent dosage on the workability of mine restoration mortar in Example 2.
[0029] Figure 6 This invention illustrates the effect of water-reducing agent dosage on the compressive strength of mine restoration mortar in Example 2.
[0030] Figure 7 This illustrates the effect of water-reducing agent on the mechanical properties of mine restoration mortar in Example 2 of this invention.
[0031] Figure 8 The XRD patterns of mine restoration mortar at different curing ages are shown in Example 2 of this invention.
[0032] Figure 9 This is a SEM image of mine restoration mortar at different curing ages in Example 2 of this invention. Detailed Implementation
[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention. Example 1
[0034] A method for preparing low-carbon self-leveling mortar for mining, the method comprising the following steps: S1. Pretreatment of papermaking sludge: After removing impurities, the papermaking sludge is placed in a cool place to dry, so that its moisture content is 10~20%, and then dried to constant weight. It is then dispersed into ≤2mm particles by ball mill for later use. S2. Pretreatment of marble tailings: After removing impurities, place the marble tailings in a cool place to dry, so that the moisture content is 10~20%, and then dry them to constant weight. Then crush them into ≤2mm particles for later use. S3. Pretreatment of quartz sludge: After removing impurities, place the quartz sludge in a cool place to dry, so that its moisture content is 10~20%, and then dry it to constant weight. Then disperse it into ≤2mm particles by ball mill for later use. S4. Pretreatment of copper tailings / lithium slag: The copper tailings and lithium slag are dried to constant weight, crushed into ≤2mm particles by a crusher, and then the copper tailings and lithium slag are mixed at a mass ratio of 1:1 to obtain a mixture. S5. Pretreatment of vanadium-titanium ore slag / copper slag / stainless steel slag: The vanadium-titanium ore slag, copper slag and stainless steel slag are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the vanadium-titanium ore slag, copper slag and stainless steel slag are mixed in a mass ratio of 1:1:1 to obtain a mixture. S6. Pretreatment of coal gasification ash / aluminum ash: The coal gasification ash and aluminum ash are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the coal gasification ash and aluminum ash are mixed at a mass ratio of 1:1 to obtain a mixture. S7. Pretreatment of phosphogypsum: (1) Dry the phosphogypsum to constant weight, disperse it to ≤2mm particles by ball milling to obtain powder 1; (2) Calcine powder 1 (heat to 140℃ at a heating rate of 5℃ / min, hold at 70min), and after cooling the calcined powder, mix it with the uncalcined powder 1 at a mass ratio of 1:1 and grind it in a ball mill to a specific surface area of 350~450m². 2 / kg, and then put the ground material into a sealed barrel to age for three days to obtain powder 2; S8. Pretreatment of waste apple tree branches and waste trees: The peeled and shortened waste apple tree branches and waste trees are dried by forced air drying until the moisture content is ≤10%, and then placed in a dry distillation kettle for carbonization using high-temperature flue gas (the temperature of the high-temperature flue gas is 500℃, and the carbonization time is 6h); then crushed to a particle size of ≤2mm by a crusher, and the crushed waste apple tree branches and waste trees particles are mixed at a mass ratio of 4:1 to obtain a carbon particle mixture of ≤2mm. S9. Compression Molding: A mixture is prepared by mixing the powders from S1, S2, S3, S4, S5, S6, and S7 in a weight ratio of 25%:30%:15%:10%:10%:5%:5%. 5% of carbon particles by weight are added to this mixture, and after thorough mixing, it is ground to a specific surface area of 300-500 m². 2 / kg, transfer to mortar mixer, add 8% water by mass of the mixture, stir well and put into mold, press into 15MPa to form patties with a thickness of 1cm and a diameter of 4cm, and dry the patties at 100℃ for 40min. S10. High-temperature calcination: The dried cake from step S9 is calcined at a high temperature. The calcination process is as follows: the temperature is raised from room temperature to 700°C at a rate of 5°C / min, and then held for 20 minutes; then the temperature is raised from 700°C to 1050°C at a rate of 10°C / min, and then held for 50 minutes; after calcination, the cake is rapidly cooled by air to obtain the high-temperature calcined product; the cooling process includes first cooling to 800°C at a rate of 18°C / min, and then cooling to room temperature at a rate of 50°C / min. S11. Pretreatment of low-carbon powder 3: The high-temperature calcined product in step S10 is crushed to ≤2mm particles by a crusher, and then ground in a ball mill to a specific surface area of 450~550m². 2 / kg, yielding 3 kg of low-carbon powder; S12. Waste cement slurry pretreatment: After screening and natural drying, waste cement slurry with a particle size <5cm is dried to constant weight, crushed to ≤2mm particles by a crusher, and then fed into a ball mill for grinding to a specific surface area of 450~550m². 2 / kg, yielding 4g of powder; S13. Pretreatment of Chinese herbal medicine residue: Dry the Chinese herbal medicine residue to constant weight; mix 11% kerosene and 96% concentrated sulfuric acid at a volume ratio of 2:1 to obtain a mixed solution; mix the Chinese herbal medicine residue and the mixed solution at a mass ratio of 25:100 and stir evenly, soak at 45℃ for 5 hours, cool to room temperature, neutralize the separated solvent with a mass percentage concentration of 25% NaOH solution to pH 7, filter, and obtain the Chinese herbal medicine residue extract; S14. Pretreatment of tofu wastewater: Add stainless steel slag to the refrigerated tofu wastewater for flocculation treatment. The flocculation time is 4 hours. After filtration, tofu wastewater filtrate is obtained. S15. Preparation of water-reducing agent: The pretreated Chinese herbal medicine residue extract in S13 and the tofu wastewater filtrate in S14 are mixed in a volume ratio of 1:1 to prepare a water-reducing agent. S16. Pre-treatment of waste wind turbine blades: The cut waste wind turbine blades are shredded and the fibers with a length of 10~13mm and a diameter of 8~11μm are screened out for later use. S17. Preparation of mine restoration mortar: Powder 2 from S7, powder 3 from S11, and powder 4 from S12 are mixed evenly in a mortar mixer at a mass ratio of 59%:17%:24% to obtain mine restoration mortar mixed powder. Add water at 38% of the mass of the mixed powder and mix evenly. Then add water-reducing agent at 0.1% of the mass of the mixed powder and mix evenly. Finally, add fiber at 1% of the mass of the mixed powder and mix evenly to obtain mine restoration mortar.
[0035] Chemical composition of powder 3 obtained in Example 1 according to step S11 (see Table 1), activity index of mine restoration mortar mixture in step S17 (see Table 2), other performance indicators and test methods of mine restoration mortar mixture (see Table 3), radioactivity results of mine restoration mortar mixture (see Table 4), technical indicators of mine restoration mortar (see Table 5), ion leaching of mine restoration mortar sample after 28 days (see Table 6).
[0036] Table 1 Chemical composition of low-carbon powder 3 in Example 1-S11
[0037] Table 2 Activity index of mine restoration mortar mixture in Example 1-S17
[0038] Table 3 Other performance indicators and test methods of mine restoration mortar mixture in Example 1-S17
[0039] Table 4. Radioactivity test results of mine restoration mortar mixtures in Examples 1-S17
[0040] Table 5 Technical Specifications of Mine Restoration Mortar in Examples 1-S17
[0041] Table 6 Ion leaching (μg / L) of mine restoration mortar sample from Example 1-S17 after 28 days Example 2
[0042] A method for preparing low-carbon self-leveling mortar for mining, the method comprising the following steps: S1. Pretreatment of papermaking sludge: After removing impurities, the papermaking sludge is placed in a cool place to dry, so that its moisture content is 10~20%, and then dried to constant weight. It is then dispersed into ≤2mm particles by ball mill for later use. S2. Pretreatment of marble tailings: After removing impurities, place the marble tailings in a cool place to dry, so that the moisture content is 10~20%, and then dry them to constant weight. Then crush them into ≤2mm particles for later use. S3. Pretreatment of quartz sludge: After removing impurities, place the quartz sludge in a cool place to dry, so that its moisture content is 10~20%, and then dry it to constant weight. Then disperse it into ≤2mm particles by ball mill for later use. S4. Pretreatment of copper tailings / lithium slag: The copper tailings and lithium slag are dried to constant weight, crushed into ≤2mm particles by a crusher, and then the copper tailings and lithium slag are mixed at a mass ratio of 2:1 to obtain a mixture. S5. Pretreatment of vanadium-titanium ore slag / copper slag / stainless steel slag: The vanadium-titanium ore slag, copper slag and stainless steel slag are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the vanadium-titanium ore slag, copper slag and stainless steel slag are mixed in a mass ratio of 1:1:2 to obtain a mixture. S6. Pretreatment of coal gasification ash / aluminum ash: The coal gasification ash and aluminum ash are dried to constant weight, crushed to a particle size of ≤2mm by a crusher, and then the coal gasification ash and aluminum ash are mixed at a mass ratio of 1:2 to obtain a mixture. S7. Pretreatment of phosphogypsum: (1) Dry the phosphogypsum to constant weight, disperse it to ≤2mm particles by ball milling to obtain powder 1; (2) Calcine powder 1 (heat to 150℃ at a heating rate of 5℃ / min, hold at 60min), and after cooling the calcined powder, mix it with the uncalcined powder 1 at a mass ratio of 1:2 and grind it in a ball mill to a specific surface area of 350~450m². 2 / kg, and then put the ground material into a sealed barrel to age for three days to obtain powder 2; S8. Pretreatment of waste apple tree branches and waste trees: The peeled and shortened waste apple tree branches and waste trees are dried by forced air drying until the moisture content is ≤10%, and then placed in a dry distillation kettle for carbonization using high-temperature flue gas (the temperature of the high-temperature flue gas is 600℃, and the carbonization time is 5h); then crushed to a particle size of ≤2mm by a crusher, and the crushed waste apple tree branches and waste trees particles are mixed at a mass ratio of 1:1 to obtain a carbon particle mixture of ≤2mm. S9. Compression Molding: The powders from S1, S2, S3, S4, S5, S6, and S7 are mixed in a weight ratio of 35%:25%:10%:10%:8%:8%:4% to obtain a mixture. 6% of the mass of carbon particles is added to this mixture, and after thorough mixing, it is ground to a specific surface area of 300-500 m². 2 / kg, transfer to mortar mixer, add 9% water by weight of the mixture, stir well and put into mold, press into 20MPa to form patties with a thickness of 2cm and a diameter of 5cm, and dry the patties at 100℃ for 40min. S10. High-temperature calcination: The dried cake from step S9 is calcined at a high temperature. The calcination process is as follows: the temperature is raised from room temperature to 700°C at a rate of 5°C / min, and then held for 20 minutes; then the temperature is raised from 700°C to 1150°C at a rate of 10°C / min, and then held for 40 minutes; after calcination, the cake is rapidly cooled by air to obtain the high-temperature calcined product; the cooling process includes first cooling to 800°C at a rate of 19°C / min, and then cooling to room temperature at a rate of 70°C / min. S11. Pretreatment of low-carbon powder 3: The high-temperature calcined product in step S10 is crushed to ≤2mm particles by a crusher, and then ground in a ball mill to a specific surface area of 450~550m². 2 / kg, yielding 3 kg of low-carbon powder; S12. Waste cement slurry pretreatment: After screening and natural drying, waste cement slurry with a particle size <5cm is dried to constant weight, crushed to ≤2mm particles by a crusher, and then fed into a ball mill for grinding to a specific surface area of 450~550m². 2 / kg, yielding 4g of powder; S13. Pretreatment of Chinese herbal medicine residue: Dry the Chinese herbal medicine residue to constant weight; mix 11% kerosene and 96% concentrated sulfuric acid at a volume ratio of 3:1 to obtain a mixed solution; mix the Chinese herbal medicine residue and the mixed solution at a mass ratio of 28:100 and stir evenly, soak at 50℃ for 4 hours, cool to room temperature, neutralize the separated solvent with a mass percentage concentration of 26% NaOH solution to pH 8, filter, and obtain the Chinese herbal medicine residue extract; S14. Pretreatment of tofu wastewater: Add stainless steel slag to the refrigerated tofu wastewater for flocculation treatment for 5 hours, then filter to obtain tofu wastewater filtrate. S15. Preparation of water-reducing agent: The pretreated Chinese herbal medicine residue extract in S13 and the tofu wastewater filtrate in S14 are mixed in a volume ratio of 1:2 to prepare a water-reducing agent. S16. Pre-treatment of waste wind turbine blades: The cut waste wind turbine blades are shredded and the fibers with a length of 10~13mm and a diameter of 8~11μm are screened out for later use. S17. Preparation of mine restoration mortar: Powder 2 from S7, powder 3 from S11, and powder 4 from S12 are mixed evenly in a mortar mixer at a mass ratio of 63%:15%:22% to obtain mine restoration mortar mixed powder. Water of 40% of the mass of the mixed powder is added and mixed evenly. Water-reducing agent of 0.2% of the mass of the mixed powder is added and mixed evenly. Finally, fiber of 2% of the mass of the mixed powder is added and mixed evenly to obtain mine restoration mortar.
[0043] Chemical composition of powder 3 obtained in Example 2 according to step S11 (see Table 7), activity index of mine restoration mortar mixture in step S17 (see Table 8), other performance indicators and test methods of mine restoration mortar mixture (see Table 9), radioactivity results of mine restoration mortar mixture (see Table 10), technical indicators of mine restoration mortar (see Table 11), ion leaching of mine restoration mortar sample after 28 days (see Table 12).
[0044] Table 7 Chemical composition of low-carbon powder 3 in Example 2-S11
[0045] Table 8 Activity index of mine restoration mortar mixture in Example 2-S17
[0046] Table 9 Other performance indicators and test methods of mine restoration mortar mixture in Example 2-S17
[0047] Table 10. Radioactivity test results of mine restoration mortar mixture in Example 2-S17
[0048] Table 11 Technical Specifications of Mine Restoration Mortar in Example 2-S17
[0049] Table 12 Ion leaching (μg / L) of mine restoration mortar sample from Example 2-S17 after 28 days Example 3
[0050] A method for preparing low-carbon self-leveling mortar for mining, the method comprising the following steps: S1. Pretreatment of papermaking sludge: After removing impurities, the papermaking sludge is placed in a cool place to dry, so that its moisture content is 10~20%, and then dried to constant weight. It is then dispersed into ≤2mm particles by ball mill for later use. S2. Pretreatment of marble tailings: After removing impurities, place the marble tailings in a cool place to dry, so that the moisture content is 10~20%, and then dry them to constant weight. Then crush them into ≤2mm particles for later use. S3. Pretreatment of quartz sludge: After removing impurities, place the quartz sludge in a cool place to dry, so that its moisture content is 10~20%, and then dry it to constant weight. Then disperse it into ≤2mm particles by ball mill for later use. S4. Pretreatment of copper tailings / lithium slag: The copper tailings and lithium slag are dried to constant weight, crushed into ≤2mm particles by a crusher, and then the copper tailings and lithium slag are mixed at a mass ratio of 1:2 to obtain a mixture. S5. Pretreatment of vanadium-titanium ore slag / copper slag / stainless steel slag: The vanadium-titanium ore slag, copper slag and stainless steel slag are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the vanadium-titanium ore slag, copper slag and stainless steel slag are mixed in a mass ratio of 2:2:1 to obtain a mixture. S6. Pretreatment of coal gasification ash / aluminum ash: The coal gasification ash and aluminum ash are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the coal gasification ash and aluminum ash are mixed at a mass ratio of 2:1 to obtain a mixture. S7. Pretreatment of phosphogypsum: (1) Dry the phosphogypsum to constant weight, disperse it to ≤2mm particles by ball milling to obtain powder 1; (2) Calcine powder 1 (heat to 160℃ at a heating rate of 5℃ / min, hold at 50min), and after cooling the calcined powder, mix it with the uncalcined powder 1 at a mass ratio of 2:1 and grind it in a ball mill to a specific surface area of 350~450m². 2 / kg, and then put the ground material into a sealed barrel to age for three days to obtain powder 2; S8. Pretreatment of waste apple tree branches and waste trees: The peeled and shortened waste apple tree branches and waste trees are dried by forced air drying until the moisture content is ≤10%, and then placed in a dry distillation kettle for carbonization using high-temperature flue gas (the temperature of the high-temperature flue gas is 700℃, and the carbonization time is 3h); then crushed to a particle size of ≤2mm by a crusher, and the crushed waste apple tree branches and waste trees particles are mixed at a mass ratio of 1:3 to obtain a carbon particle mixture of ≤2mm. S9. Compression Molding: The powders from S1, S2, S3, S4, S5, S6, and S7 are mixed in a weight ratio of 26%:35%:20%:5%:5%:6%:3% to obtain a mixture. 8% (by weight) of carbon particles are added to this mixture, and after thorough mixing, it is ground to a specific surface area of 300-500 m². 2 / kg, transfer to mortar mixer, add 10% water by weight of the mixture, stir well and put into mold, press into 25MPa to form patties with a thickness of 2cm and a diameter of 6cm, and dry the patties at 100℃ for 40min. S10. High-temperature calcination: The dried cake from step S9 is calcined at a high temperature. The calcination process is as follows: the temperature is raised from room temperature to 700°C at a rate of 5°C / min, and then held for 20 minutes; then the temperature is raised from 700°C to 1250°C at a rate of 10°C / min, and then held for 30 minutes; after calcination, the cake is rapidly cooled by air to obtain the high-temperature calcined product; the cooling process includes first cooling to 800°C at a rate of 20°C / min, and then cooling to room temperature at a rate of 80°C / min. S11. Pretreatment of low-carbon powder 3: The high-temperature calcined product in step S10 is crushed to ≤2mm particles by a crusher, and then ground in a ball mill to a specific surface area of 450~550m². 2 / kg, yielding 3 kg of low-carbon powder; S12. Waste cement slurry pretreatment: After screening and natural drying, waste cement slurry with a particle size <5cm is dried to constant weight, crushed to ≤2mm particles by a crusher, and then fed into a ball mill for grinding to a specific surface area of 450~550m². 2 / kg, yielding 4g of powder; S13. Pretreatment of Chinese herbal medicine residue: Dry the Chinese herbal medicine residue to constant weight; mix 11% kerosene and 96% concentrated sulfuric acid at a volume ratio of 3:1 to obtain a mixed solution; mix the Chinese herbal medicine residue and the mixed solution at a mass ratio of 30:100 and stir evenly, soak at 55℃ for 3 hours, cool to room temperature, neutralize the separated solvent with a mass percentage concentration of 28% NaOH solution to pH 9, filter, and obtain the Chinese herbal medicine residue extract; S14. Pretreatment of tofu wastewater: Add stainless steel slag to the refrigerated tofu wastewater for flocculation treatment. The flocculation time is 6 hours. After filtration, tofu wastewater filtrate is obtained. S15. Preparation of water-reducing agent: The pretreated Chinese herbal medicine residue extract in S13 and the tofu wastewater filtrate in S14 are mixed in a volume ratio of 2:1 to prepare a water-reducing agent. S16. Pre-treatment of waste wind turbine blades: The cut waste wind turbine blades are shredded and the fibers with a length of 10~13mm and a diameter of 8~11μm are screened out for later use. S17. Preparation of mine restoration mortar: Powder 2 from S7, powder 3 from S11, and powder 4 from S12 are mixed evenly in a mortar mixer at a mass ratio of 67%:13%:20% to obtain mine restoration mortar mixed powder. Water of 42% of the mass of the mixed powder is added and mixed evenly. Water-reducing agent of 0.3% of the mass of the mixed powder is added and mixed evenly. Finally, fiber of 3% of the mass of the mixed powder is added and mixed evenly to obtain mine restoration mortar.
[0051] Chemical composition of powder 3 obtained in Example 3 according to step S11 (see Table 13), activity index of mine restoration mortar mixture in step S17 (see Table 14), other performance indicators and test methods of mine restoration mortar mixture (see Table 15), radioactivity results of mine restoration mortar mixture (see Table 16), technical indicators of mine restoration mortar (see Table 17), ion leaching of mine restoration mortar sample after 28 days (see Table 18).
[0052] Table 13 Chemical composition of low-carbon powder 3 in Example 3-S11
[0053] Table 14 Activity index of mine restoration mortar mixture in Example 3-S17
[0054] Table 15 Other performance indicators and test methods of mine restoration mortar mixture in Example 3-S17
[0055] Table 16. Radioactivity test results of mine restoration mortar mixtures in Examples 3-S17
[0056] Table 17 Technical Specifications of Mine Restoration Mortar in Example 3-S17
[0057] Table 18 Ion leaching (μg / L) of mine restoration mortar sample from Example 3-S17 after 28 days
[0058] The present invention will be further described below with reference to the accompanying drawings: Analysis of the composition, morphology and properties of the high-temperature calcination product in step S10 of Example 2 1. Mineral composition of the high-temperature calcination product The mineral composition of the high-temperature calcined material prepared in step S10 was qualitatively and quantitatively analyzed using X-ray diffraction. The results are shown in [Figure number missing]. Figure 1 As shown. From Figure 1 It can be seen that the prepared high-temperature calcined mineral phase is C2S, C4AF, and C also exist 12 A7, C3A, and trace amounts of CaSO4. Typically fired at room temperature within the range of 950~1100℃. Mainly composed of C2AS, CaO, Al2O3 and SiO2 It begins to form at 1050℃, and when the temperature rises to 1050~1150℃... It begins to form in large quantities, and C2AS disappears. At the 1150°C set in Example 2, due to the addition of papermaking sludge and carbon particles to the raw material system, the furnace temperature has already reached approximately 1250°C. Figure 1 middle The diffraction characteristic peaks of β-C2S are significant. If the calcination temperature continues to rise to 1275 or 1300℃, β-C2S minerals will gradually form, and the calcined product will exhibit... β-C2S and The main focus is on C. 12 A7 and C3A minerals will decompose. Holding time is a crucial factor influencing the degree of mineral phase formation. Powder 3, obtained under the design calcination temperature of 1150℃ and a holding time of 40 minutes, and rapid cooling conditions with blowing air, aims to improve the quality of the high-temperature calcination product by controlling the cooling rate; specifically, slow cooling initially promotes the decomposition of some C3S into β-C2S and CaO. Extending the holding time will lead to… The content of C4AF and C3A decreases, while the content of C3A increases. C4AF and C3A melt with MgO and alkali at 1150℃ to form a liquid phase. The increase in the amount of liquid phase promotes the absorption of f-CaO, achieving the requirement of f-CaO ≤ 1.5% for cement clinker (see Table 19). When the heat preservation time exceeds 40 minutes, it easily causes… Synthesized and then decomposed, leading to The decrease in quantity can be described by formulas (1) and (2): (1) (2)
[0059] Table 19. Results of f-CaO content determination in high-temperature calcination products (wt.%)
[0060] 2. Microstructure of the high-temperature calcination products Figure 2 and Figure 3 SEM-EDS images of powder 3, calcined at 1150℃ and held for 40 min, were obtained under rapid cooling conditions. Figure 2The mineral particles are mainly round or elliptical with smooth surfaces. The boundaries between the crystal particles are clear, and the particles are more tightly bonded. This particle morphology facilitates subsequent grinding and processing, has a relatively large surface area, and has better hydration properties.
[0061] Depend on Figure 3 The EDS spectra and statistical analysis (see Table 20) show that the minerals at points A and B are both C2S. C2S with a composition similar to point B is more common in this high-temperature calcination product. The Ca / Si ratio at point A is 2.3, indicating a higher concentration of impurity ions in the solid solution at point A, primarily K+ and Na+ alkali metal ions. Furthermore, the crystallization is incomplete, with significant lattice distortion. The doping of these impurity ions may have altered the silicon-oxygen tetrahedron (SiO4) of the C2S crystal. 4- The orientation of C2S at point B is 2.1, and it also contains solid solutions of aluminum, iron, magnesium, and small amounts of potassium and sodium. At point C, a partially hollow tubular structure appears; EDS analysis indicates that it is primarily a solid solution of C4AF, with some silicon, magnesium, and alkali metal ions as dopants.
[0062] At the same time from Figure 2 It can be seen that C2S particles are generally below 15 μm, and the surface exhibits numerous microcracks. This may be due to the decrease in crystal symmetry during the transformation from the high-temperature to the low-temperature crystal form during cooling, or it may be a dissolution channel for dopant ions during the cooling process, as the low-temperature crystal form is less prone to solidifying impurity ions compared to the high-temperature crystal form. The microcracks on the sample surface are also likely due to the increased crystallization pull caused by dopants in the C2S crystal, leading to cracking defects. The smaller silicon C2S crystal size and significant crystal cracking defects may be the reasons for increased clinker hydration reactivity.
[0063] Table 20 Figure 3 Statistical results of analysis of points A, B, and C (mol)
[0064] 3. Properties of high-temperature calcined products In Example 2, an appropriate amount of gypsum was added to powder 3 prepared from the high-temperature calcination product. A mortar strength test was conducted with a water-cement ratio of 0.5 and a sand-cement ratio of 3. A reference cement was used as a control sample, and its mortar compressive strength was tested using the same water-cement ratio and sand-cement ratio. The compressive strength was measured at 1 day, 3 days, 7 days, 28 days, and 90 days of curing. The compressive strengths of the reference cement and powder 3 mortar were obtained as follows: Figure 4As shown in the figure, the 1-day and 3-day compressive strength of cement prepared from powder 3 is significantly higher than that of the reference cement. It typically reaches the 7-day strength level of the reference cement at 3 days. The 28-day strength of cement prepared from powder 3 is comparable to that of the reference cement, and with the extension of the curing age, its 90-day strength exceeds that of the reference cement. The strength performance of powder 3 depends on the optimized matching relationship of various minerals within its system, effectively ensuring the optimal ratio of several minerals in powder 3, guaranteeing synergistic hydration among the minerals, and promoting the stable performance of powder 3's strength. Furthermore, the performance of powder 3 is similar to or even better than that of silicate cement clinker, indicating that powder 3 can be widely used to replace traditional silicate cement.
[0065] Analysis of the properties, composition and morphology of the mine restoration mortar in step S17 of implementation example 2 1. The effect of water-reducing agents on the properties of mine restoration mortar
[0066] Water-reducing agents can reduce water consumption, improve fluidity, reduce porosity, and also have a positive effect on durability and mechanical properties. When high-efficiency water-reducing agents are added to cement, their hydrophilic chains adsorb onto the cement particles, and their polar ends extend into the water, reducing the surface tension of the water and making the cement particles hydrophilic. A layer of water dipoles is generated on the particle surface, preventing flocculation and maintaining good dispersibility of the cement. Simultaneously, different types of high-efficiency water-reducing agents adsorbed on the surface of cement particles inhibit the formation and growth of hydration product crystals, thus affecting the structural properties of the hydration products. This invention, combined with Example 2, analyzes the impact of water-reducing agents on the performance of mine restoration mortar. Figures 5-7 As shown. With a fixed water-to-mixed powder mass ratio of 0.4:1, after adding a water-reducing agent prepared from traditional Chinese medicine residue and tofu wastewater, the spread of the mine restoration mortar significantly increased (see...). Figure 5 The water-reducing agent exhibits good dispersion effects on mine restoration mortar, significantly improving the mortar's spreadability even at low dosages. The spreadability of the mine restoration mortar without water-reducing agent was only 143 mm. The spreadability of the mine restoration mortar system with 0.05% water-reducing agent increased by 8.39% to 155 mm, and the spreadability of the mine restoration mortar system with 0.30% water-reducing agent increased by 58.0%, reaching a flow spreadability of 226 mm. The increase in flowability was greatest at a water-reducing agent dosage of 0.15%, after which the increasing trend in flowability gradually decreased with further increases in water-reducing agent dosage.
[0067] Figure 5The study also demonstrated the effect of water-reducing agent dosage on the standard consistency water requirement of mine restoration mortar. With the addition of water-reducing agent, the standard consistency water requirement of the mine restoration mortar system gradually decreased, which is the opposite trend to the flow spread. The study showed that the water-reducing agent had a better dispersion effect on mine restoration mortar under neutral or weakly alkaline conditions (see Table 11, system pH=8.0). When powder 3 was added to phosphogypsum, the mortar gradually changed from its original weakly acidic state to neutral or alkaline, thus improving the effect of the water-reducing agent. Simultaneously, powder 3 itself has better adaptability to water-reducing agent than phosphogypsum; replacing part of the phosphogypsum with powder 3 makes the overall system more adaptable to water-reducing agent than phosphogypsum. The synergistic effect of these two aspects resulted in a reduction in the amount of water-reducing agent required and an improvement in dispersion.
[0068] The effect of water-reducing agents on the mechanical properties of mine restoration mortar systems is shown in the figure. Figure 6 and Figure 7 .from Figure 6 The graph shows the development trend of 24-hour compressive strength and 28-day oven-dry compressive strength of mine repair mortar samples when the water-reducing agent dosage is 0%, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, and 0.30%. As can be seen from the graph, with the increase of water-reducing agent dosage, the 24-hour compressive strength and 28-day oven-dry compressive strength of the mine repair mortar samples generally show a trend of first increasing and then decreasing. The 24-hour compressive strength and 28-day oven-dry compressive strength of the mine repair mortar samples without water-reducing agent are 8.2 MPa and 27.5 MPa, respectively, meeting the technical requirements of ≥2.0 MPa and ≥25 MPa in the standard JC / T 1023-2021 "Gypsum-based Self-leveling Mortar". The 24-hour compressive strength and 28-day oven-dry compressive strength were highest when the water-reducing agent dosage was 0.20%, reaching 11.9 MPa and 33.4 MPa respectively. These values represented increases of 45.1% and 21.5% respectively compared to the compressive strength of the mine restoration mortar sample without water-reducing agent. Comprehensive analysis shows that in Example 2, the water-reducing agent achieved the best effect when the dosage was 0.20%. With a water-reducing agent dosage of 0.20%, the technical indicators of the mine restoration mortar all met the requirements of the technical specifications in JC / T 1023-2021, "Gypsum-based Self-leveling Mortar". The 24-hour flexural strength and 28-day oven-dry flexural strength of the mine restoration mortar samples reached 3.7 MPa and 9.6 MPa, respectively; the 24-hour compressive strength and 28-day oven-dry compressive strength reached 11.9 MPa and 33.4 MPa, respectively; and the 28-day oven-dry tensile bond strength reached 2.3 MPa (see...). Figure 7 ).
[0069] 2. Composition and Morphology of Mine Restoration Mortar
[0070] Figure 8XRD patterns of hydration products after adding 0.20% water-reducing agent to mine restoration mortar and curing for 24 hours, 3 days, and 28 days. From... Figure 8 It can be seen that the main hydration products generated in the cured mine restoration mortar samples are CaSO4·2H2O, CSH gel, and ettringite (AFt). The composition of the hydration products indicates that the addition of aluminate powder 2 has a certain inhibitory effect on the hydration formation of hemihydrate gypsum, and therefore also has a certain inhibitory effect on the exothermic hydration of phosphogypsum. After 24 hours of hydration, the main observed hydration products were CaSO4·2H2O, CSH gel, and ettringite (AFt). No diffraction peak was observed for CaSO4·0.5H2O, indicating that the unhydrated hemihydrate gypsum continued to hydrate in the subsequent hydration reaction, or reacted with aluminate powder 2 to form AFt. During the hydration reaction, a certain amount of ettringite was generated by aluminate powder 2 and phosphogypsum, playing an interpenetrating role in the gypsum skeleton structure. Simultaneously, the gel generated by the hydration of aluminate cement itself encapsulates and fills the skeleton structure, making the hardened body structure dense and increasing its strength. With the extension of curing time… Figure 8 The diffraction peaks of the hydration products CaSO4·2H2O, CSH gel, and ettringite (AFt) gradually increased, the crystals of the hydration products became coarser, and the aspect ratio became smaller. The hardened structure of the mine restoration mortar became significantly denser and more compact, which is the main reason for the improvement in the strength and toughness of the mine restoration mortar sample.
[0071] Figure 9 The microstructure of hydration products after adding 0.20% water-reducing agent to mine restoration mortar and curing for 24 hours, 3 days, 7 days, and 28 days was determined. Figure 9 (a) SEM images taken after 24 hours of hydration show that the CaSO4·2H2O in the water-reducing agent-incorporated system consists of needle-like or rod-shaped crystals with a large aspect ratio. The crystals grow rapidly along the c-axis, with the c-axis length concentrated between 8 and 10 μm. The CaSO4·2H2O crystals are relatively large, with few inter-crystal bonding points, resulting in a loose overall structure with numerous pores. Hydration for 3 days (… Figure 9 (b) The CaSO4·2H2O crystals are relatively tightly packed, with a small number of granular CaSO4·2H2O crystals observed. The c-axis length of most CaSO4·2H2O crystals shows no significant change. (7 days after hydration) Figure 9 In (c), CaSO4·2H2O crystals grow along the c-axis, becoming shorter with lengths mainly concentrated between 4 and 6 μm. Some granular CaSO4·2H2O crystals are also observed, indicating that the water-reducing agent promotes selective nucleus adsorption, which is beneficial for CaSO4·2H2O crystals. 2 + A stable complex forms on the crystal nucleus surface, hindering further hydration of phosphogypsum and severely suppressing c-axis development during crystal growth. (28 days of hydration) Figure 9In the hardened body of (d), some plate-like CaSO4·2H2O crystals were found, and the crystals were coarsened with a significantly reduced aspect ratio. The CaSO4·2H2O crystals grew in close co-directional packing, resulting in a more compact structure, which increased the mechanical properties of the system.
[0072] According to the dissolution and crystallization theory of gypsum hydration, the growth of CaSO4·2H2O includes both the dissolution of CaSO4·0.5H2O and the crystallization of CaSO4·2H2O crystals. Since crystal growth is a surface reaction, the anisotropy of the growth rate of the crystal nucleus during the growth process leads to differences in crystal morphology. 2+ and [SO4] 2- The binding energy and bonding forms differ along different crystal axes, with faster growth along the a-axis and c-axis, resulting in CaSO4·2H2O crystals often exhibiting a long columnar shape. The adsorption of water-reducing agents is a prerequisite for improving the performance of the gypsum system, and the different adsorption effects lead to variations in the influence of water-reducing agents on the growth process of dihydrate gypsum crystals. Since the incorporation of water-reducing agents inhibits the temperature rise during the acceleration phase, which is the growth stage of CaSO4·2H2O crystals, it hinders the growth of CaSO4·2H2O crystals along the c-axis, which is consistent with the conclusions of Guan et al.
[0073] In summary, the mine restoration mortar prepared using solid waste in this invention has improved upon the technical indicators such as physical and mechanical properties (workability and mechanical properties) compared to the requirements of the standard JC / T 1023-2021 "Gypsum-based Self-leveling Mortar", and is superior to existing products on the market, making it worthy of vigorous promotion.
[0074] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing low-carbon self-leveling mortar for mining, the method comprising the following steps: S1. Pretreatment of papermaking sludge: After removing impurities, the papermaking sludge is placed in a cool place to dry, so that its moisture content is 10~20%, and then dried to constant weight. It is then dispersed into ≤2mm particles by ball mill for later use. S2. Pretreatment of marble tailings: After removing impurities, place the marble tailings in a cool place to dry, so that the moisture content is 10~20%, and then dry them to constant weight. Then crush them into ≤2mm particles for later use. S3. Pretreatment of quartz sludge: After removing impurities, place the quartz sludge in a cool place to dry, so that its moisture content is 10~20%, and then dry it to constant weight. Then disperse it into ≤2mm particles by ball mill for later use. S4. Pretreatment of copper tailings / lithium slag: Dry the copper tailings and lithium slag separately to constant weight, crush them into ≤2mm particles by crusher, and then mix the copper tailings and lithium slag at a mass ratio of 1~2:1~2 to obtain a mixture. S5. Pretreatment of vanadium-titanium ore slag / copper slag / stainless steel slag: The vanadium-titanium ore slag, copper slag and stainless steel slag are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the vanadium-titanium ore slag, copper slag and stainless steel slag are mixed in a mass ratio of 1~2:1~2:1~2 to obtain a mixture. S6. Pretreatment of coal gasification ash / aluminum ash: The coal gasification ash and aluminum ash are dried to constant weight, crushed to particle size ≤2mm by a crusher, and then the coal gasification ash and aluminum ash are mixed at a mass ratio of 1~2:1~2 to obtain a mixture. S7. Pretreatment of phosphogypsum: (1) Dry the phosphogypsum to constant weight, disperse it to ≤2mm particles by ball milling to obtain powder 1; (2) Calcine powder 1, and after cooling, mix the powder obtained by calcination with the uncalcined powder 1 at a mass ratio of 1~2:1~2 and grind it in a ball mill to a specific surface area of 350~450m². 2 / kg, and then put the ground material into a sealed barrel to age for three days to obtain powder 2; S8. Pretreatment of waste apple branches and waste trees: The peeled and pruned waste apple branches and waste trees are dried by forced air drying until the moisture content is ≤10%, and then placed in a dry distillation kettle for carbonization using high-temperature flue gas; then crushed to a particle size of ≤2mm by a crusher, and the crushed waste apple branches and waste trees particles are mixed at a mass ratio of 1~4:1~3 to obtain a carbon particle mixture of ≤2mm. S9. Compression Molding: A mixture is prepared by mixing the powders from S1, S2, S3, S4, S5, S6, and S7 in a weight ratio of 25-35%:25-35%:10-20%:5-10%:5-10%:5-8%:3-5%. 5-8% (by weight) of carbon particle mixture is added to this mixture. After thorough mixing, the mixture is ground to a specific surface area of 300-500 m². 2 / kg, transfer to mortar mixer, add 8~10% water by weight of the mixture, stir well, put into mold, press into patties, and dry the patties at 100℃ for 40min; S10. High-temperature calcination: The cake dried in step S9 is calcined at high temperature. After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. S11. Pretreatment of low-carbon powder 3: The high-temperature calcined product in step S10 is crushed to ≤2mm particles by a crusher, and then ground in a ball mill to a specific surface area of 450~550m². 2 / kg, yielding 3 kg of low-carbon powder; S12. Waste cement slurry pretreatment: After screening and natural drying, waste cement slurry with a particle size <5cm is dried to constant weight, crushed to ≤2mm particles by a crusher, and then fed into a ball mill for grinding to a specific surface area of 450~550m². 2 / kg, yielding 4g of powder; S13. Pretreatment of Chinese herbal medicine residue: Dry the Chinese herbal medicine residue to constant weight; mix 11% kerosene and 96% concentrated sulfuric acid at a volume ratio of 2-3:1 to obtain a mixed solution; mix the Chinese herbal medicine residue and the mixed solution at a mass ratio of Mix 25~30:100 and stir evenly. Soak at 45~55℃ for 3-5 hours. Cool to room temperature. Neutralize the separated solvent with 25%~28% NaOH solution to pH 7-9. Filter to obtain the extract of Chinese herbal medicine residue. S14. Pretreatment of tofu wastewater: Add stainless steel slag to the refrigerated tofu wastewater for flocculation treatment. The flocculation time is 4-6 hours. Filter to obtain tofu wastewater filtrate. S15. Preparation of water-reducing agent: The pretreated Chinese herbal medicine residue extract in S13 and the tofu wastewater filtrate in S14 are mixed in a volume ratio of 1~2:1~2 to prepare a water-reducing agent. S16. Pre-treatment of waste wind turbine blades: The cut waste wind turbine blades are shredded and the fibers with a length of 10~13mm and a diameter of 8~11μm are screened out for later use. S17. Preparation of self-leveling mortar: Powder 2 from S7, powder 3 from S11, and powder 4 from S12 are mixed evenly in a mortar mixer at a mass ratio of 59~67%:13~17%:20~24% to obtain self-leveling mortar mixed powder. Add water at a mass ratio of 38~42% of the mixed powder and mix evenly. Then add water-reducing agent at a mass ratio of 0.1~0.3% of the mixed powder and mix evenly. Finally, add fiber at a mass ratio of 1~3% of the mixed powder and mix evenly to obtain self-leveling mortar.
2. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, The calcination of powder 1 in step S7 is as follows: the temperature is increased to 140℃~160℃ at a heating rate of 5℃ / min, and held at the temperature for 50~70min.
3. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, In step S8, carbonization is performed with the following conditions: the temperature of the high-temperature flue gas is 500~700℃, and the carbonization time is 3~6h.
4. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, In step S9, the powders in S1, S2, S3, S4, S5, S6, and S7 are mixed in a weight ratio of 35%:25%:10%:10%:8%:8%:4% to obtain the mixture.
5. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, In step S9, the pressing pressure is 15~25 MPa, the cake thickness is 1~2 cm, and the diameter is 4~6 cm.
6. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, The high-temperature calcination in step S10 is as follows: the temperature is increased to 700°C at a heating rate of 5°C / min, and then held for 20 min; then the temperature is increased to 1050~1250°C at a heating rate of 10°C / min, and held for 30~50 min.
7. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, The cooling process in step S10 includes first cooling to 800°C at a wind speed of 18-20°C / min, and then cooling to room temperature at a speed of not less than 50°C / min.
8. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, In step S10, the high-temperature calcination involves heating from 700°C to 1150°C at a rate of 10°C / min and holding at that temperature for 40 minutes.
9. The method for preparing low-carbon self-leveling mortar for mining according to claim 1, characterized in that, In step S17, the mass ratio of powder 2 in S7, powder 3 in S11, and powder 4 in S12 of the self-leveling mortar mixing powder is 63%:15%:22%.
10. The method for preparing low-carbon self-leveling mortar for mining according to any one of claims 1 to 9, wherein in step S17, 0.2% by weight of water-reducing agent of the mixed powder is added.
Citation Information
Patent Citations
Method for synergistically preparing foundation pit backfill material by utilizing multi-element solid waste
CN115259817A
Lithium slag doped all-solid waste paste filling material and preparation method thereof
CN117185764A